Dimension Confinement Effect Boosted Ultrasensitive Colorimetric Signal Concentrating. Issue 16 (25th May 2020) - Wang, Peixian; Cai, Zhenzhen; Li, Jiguang; Li, Yushu; Zu, Baiyi; Dou, Xincun
Abstract: To understand the underlying fundamental mechanism affecting the optical sensitivity of a paper‐based substrate, a layered polyvinyl alcohol (PVA) network paper is proposed considering the physical geometry and chemical composition required to enhance the sensitivity. It is verified both theoretically and experimentally that the dimension confinement effect introduced by the Steiner network, layered and pore structures, as well as massive hydroxyl groups, play an essential role in enhancing the concentration signal on the surface. Trace chlorate droplets and particles are considered representative examples to prove the excellent structural design‐induced performance of the PVA network paper. A practical mass detection from potassium chlorate solution and particles could be as low as 9.9 pg and 0.34 fg, respectively, and the corresponding naked‐eye observation limit could reach 0.69 ng and 1.6 pg, respectively, assuming the distinguishable size for human eyes is 100 µm. Further, the detection time could be far less than 2 s, which is remarkably superior than the detection performance of the parallel filter paper counterpart. The dimension confinement effect demonstrated here is expected to be of great importance for advancing the development of paper‐based trace detection. Abstract : The dimension confinement effect introduced by the Steiner network, layered and pore structures, as well as a massive hydroxyl group are theoretically and experimentally verified by a polyvinyl alcohol (PVA) network paper, and a remarkably superior detection performance in both detection limit and detection time toward trace chlorate droplets and particles is observed due to the greatly boosted concentration signal on the surface.